Shoulder rotator strength in judo athletes: A cross-sectional study with different experience levels - Detanico, D.; Ghedini Gheller, R.; Saldanha Da Silva Athayde, M.; Lima Kons, R. (Isokinetics and Exercise Science, 2024)
BACKGROUND: Judo practice requires high effort from athletes, mainly focused on the upper limbs, involving the shoulder complex.